Accuracy of Demirjian's 8 teeth method for age prediction in South Indian children: A comparative study - Rezwana Begum Mohammed; Baratam Srinivas; Praveen Sanghvi; Gajjarapu Satyanarayana; Meera Gopalakrishnan; B Vamsi Pavani (Wolters Kluwer Medknow Publications, 2015)
Introduction: Demirjian's method of tooth development is most commonly used to assess age in individuals with emerging teeth. However, its application on numerous populations has resulted in wide variations in age estimates and consequent suggestions for the method's adaptation to the local sample. Original Demirjian's method utilized seven mandibular teeth, to which recently third molar is added so that the method can be applied on a wider age group. Furthermore, the revised method developed regression formulas for assessing age. In Indians, as these formulas resulted in underestimation, India-specific regression formulas were developed recently. The purpose of this cross-sectional study was to evaluate the accuracy and applicability of original regression formulas (Chaillet and Demirjian 2004) and India-specific regression formulas (Acharya 2010) using Demirjian's 8 teeth method in South Indian children of age groups 9-20 years. Methods: The present study consisted of 660 randomly selected subjects (330 males and 330 females) were in the aged ranging from 9 to 20 years divided into 11 groups according to their age. Demirjian's 8 teeth method was used for staging of teeth. Results: Demirjian's method underestimated the dental age (DA) by 1.66 years for boys and 1.55 years for girls and 1.61 years in total. Acharya's method over estimated DA by 0.21 years for boys and 0.85 years for girls and 0.53 years in total. The absolute accuracy was better for Acharya's method compared with Demirjian method. Conclusion: This study concluded that both the Demirjian and Indian regression formulas were reliable in assessing age making Demirjian's 8 teeth method applicable for South Indians.